Gender Nonconformity, Homophobic Peer Victimization, and Mental Health: How Same-Sex Attraction and Biological Sex Matter. Issue 1 (2nd January 2016) - van Beusekom, Gabriël; Baams, Laura; Bos, Henny M. W.; Overbeek, Geertjan; Sandfort, Theo G. M.
Abstract : We assessed whether homophobic name-calling accounts for the relationship between gender nonconformity and mental health (social anxiety and psychological distress) in a sample of 1, 026 Dutch adolescents (boys: n = 517) ages 11 to 16 ( M age = 13.4). We also explored whether this hypothesized mediation differs by sexual attraction and biological sex. Data were collected by means of paper-and-pencil questionnaires at five secondary schools located in urban areas in the Netherlands. Mediation analysis indicated that gender nonconformity was related to both social anxiety and psychological distress partially via homophobic name-calling. Moderated mediation analysis further showed that the mediating role of homophobic name-calling varied according to levels of same-sex attraction (SSA) and biological sex. The mediation effects increased in magnitude when levels of SSA increased and were significant only for adolescents with mean and high levels of SSA. The mediation effects were significant for boys and girls in general, although the mediation effects were stronger for boys than for girls. Our findings emphasize the importance of research and school-level interventions to focus on factors that promote acceptance of cross-gender behavior among adolescents.